Pelatihan Metode Dan Analisis Studi Ekosistem Mangrove Pada Mahasiswa Ilmu Kelautan Universitas Pattimura - Rahman Rahman; Martha Luana Wattimena; Frijona F Lokollo (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mangroves provide various ecosystem services such as ecological, economic and social benefits for humans and the surrounding environment. As agents of future change, students have an important role in contributing new knowledge and innovative solutions for the preservation and management of mangrove ecosystems. Training activities are carried out to increase student perceptions of mangrove ecosystems and participation in research activities on current mangrove topics, namely blue carbon dynamics. Activities are evaluated through an open questionnaire with a Likert scale and analysis of the perception index. The results of the activity showed that the training activities on methods and analysis of mangrove ecosystem studies were very effective in increasing students' perceptions and understanding of mangrove ecosystems (IP = 0.71). In particular, training on the dynamics of blue carbon in mangroves can spark student interest, thereby increasing participation in research in this field. It can be seen from the seriousness of the students to determine the title that will be carried out as the final assignment in completing the study.